2003
DOI: 10.1046/j.1365-2036.2003.01520.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in oesophageal and gastric cancer incidence, mortality and survival in England and Wales 1971–1998/1999

Abstract: SUMMARYBackground: In England and Wales, 7% of cancers diagnosed in 1997 were oesophageal or gastric cancer. Aim: To review the epidemiology of these cancers in England and Wales using cancer registration data from 1971 to 1998 and mortality data from 1971 to 1999. Methods: We calculated age-specific and age-standardised incidence and mortality rates; crude and relative survival by age group; age-standardised relative survival; and relative survival by socio-economic status. Results: The age-standardised incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 17 publications
1
36
0
1
Order By: Relevance
“…Thus marked changes in mortality rates, either increased or decreased, usually indicate that a new environmental agent has been introduced into or removed from the population in question. Compared with many other countries [11][12][13][14][15][16][17][18] , all cancer mortality in Henan Province varied slightly over the past 25 years. Although mortality rates varied widely in specific cancers, cancers of the esophagus, stomach, liver and lung accounted for over 86 % of all cancer deaths in Henan Province.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus marked changes in mortality rates, either increased or decreased, usually indicate that a new environmental agent has been introduced into or removed from the population in question. Compared with many other countries [11][12][13][14][15][16][17][18] , all cancer mortality in Henan Province varied slightly over the past 25 years. Although mortality rates varied widely in specific cancers, cancers of the esophagus, stomach, liver and lung accounted for over 86 % of all cancer deaths in Henan Province.…”
Section: Discussionmentioning
confidence: 99%
“…Stomach cancer mortality rates did not change substantially during the period studied. Inversely, gastric cancer incidence and mortality rates showed a consistent decline in recent decades world-wide [12][13][14][15]21,22,35] . Liver cancer mortality rates for males markedly increased over the last two decades, from 17 per 100 000 in 1974-1976 to 32 per 100 000 in 1996-1998, for females from 8 per 100 000 in 1974-1976 to 16 per 100 000 in 1996-1998.…”
Section: Discussionmentioning
confidence: 99%
“…Since the mid 1990s its incidence has exceeded that for SCC [14,15,16]. The rise in incidence is most marked in the white male population, reaching about 5/100 000 for the white males in North America and 8-12/100 000 for white males in the highest incidence countries of Australia and the UK [7,13,17,18,19,20,21,22]. This represents an increase of about 400-800% from the 1970s and is about four times greater than the incidence for black males in the United States.…”
Section: Adenocarcinomamentioning
confidence: 99%
“…The current paper reveals the influence of socioeconomic determinants on GC survival risk factors, contributing to previous studies identifying age, race, and socioeconomic factors as significant predictors of survival outcomes for GC patients. In 2003, Newnham reported a significant association between five-year survival rate and deprivation for women with GC, but not for men with GC in either sex (22). Likewise, Whynes (2003) revealed that females in the least-deprived SES tended to live an average of 1.1 years longer than females in the most-deprived SES (23).…”
Section: Discussionmentioning
confidence: 99%